Determinación del valor razonable e incidencias en los métodos contables, un reto para las pymes agrícolas (2021)
This article identifies the methods for the recognition and measurement of biological assets in agricultural SMEs in Colombia, their importance in the current context and the challenge they are facing, which is the determination of fair value since, Agricultural Smes are not allocating the correct value in the valuation of the biological asset at the initial time and during its growth and production stages, exposing themselvesto risks that may present unexpected losses. These are faced with low profitability resulting from inadequate procedures that increase production costs and lower the selling price of products, this was done by seeking knowledge of fair value measurement techniques that enhance process efficiency and frame a sustainable potential in the production of biological assets. In this way we followed an exploratory methodology, locating database as, open-access documentary sources to extract the most relevant information by placing descriptors such as: Accounting Models, Biological Asset, Agricultural SMEs, Fair Value, recognition, measurement, cost and market.